Intellectual Capital Impact On Contextual Performance: Applied Study In Higher Education Institutions In The Sultanate Of Oman - Musallam Said Musallam Hardan; Tarig Mohammed Salih Atiya; Khatijah Binti Othman (OCERINT International, 2024)
Volume: 5 Issue:14